The Washington consensus in Brazil: conservative stabilization and stagnation - Carretoni Vaz, Vinícius Rezende (2021)
Since the 1970s, several Latin American countries have started to adhere to economic policies stemming from neoliberal thinking, starting in Chile, with a greater degree of “experimentation” and in the midst of a dictatorship. Subsequently, mainly after the production of the document entitled “Washington Consensus”, this economic thought passes through an emperor in the region. Brazil, unlike Chile, was one of the last countries to practice policies based on this thought and only after the democratization process, which leads us to a question of what are the consequences of the Washington consensus in Brazil. Among the hypotheses, we have the stabilization of specific macroeconomic indices and greater economic openness. This article aims to detail the reflexes of adherence to neoliberalism in economic policy and affect these Brazilian policies.